Effect of exfoliated graphene on thermal conductivity enhancements of graphene-ironoxide hybrid nanofluids: Experimental investigation and effective medium theories - Arifutzzaman, A.; Ismail, Ahmad Faris; Alam, Md. Zahangir; Khan, Ahsan Ali; Saidur, Rahman (2021)
Reasoning of particular mechanism of anomalous thermal transport behaviours are not identified yet for the nanofluids. In this study, iron oxide (Maghemite: MH) and graphene (Gr) flake dispersed deionized water (DW) hybrid nanofluid system were developed for the first time to evaluate the thermal conductivity (TC) enhancements along with the analysis of anomalous TC behavior implementing modified effective medium theories (EMTs). A solvo-thermal two-step method was used to develop the MH nanoparticle and exfoliated Gr flake dispersed hybrid nanofluids with different compositions. Stability of as-prepared hybrid nanofluids were monitored using Ultraviolet-Visible (UV-Vis) spectroscopy. The maximum sedimentation rate was observed ~ 8.4 % after 600 hours. The results showed an overall maximum TC enhancement of ~ 43 % at 25 °C. EMTs were modified with the consideration of flat geometry of Gr flake. It is found that, modified EMTs with the crumpled factor (due to the non-flatness or crumple of Gr flake) of ~ 0.205 the predicted effective TC enhancements are agreed with the experimental TC’s of Gr-NMP/MH-DW hybrid nanofluids samples. The estimated crumple factor value of exfoliated Gr flakes using images analysis was also found nearly similar (~ 0.232). This agreement exposed that, Gr flake’s with negligible thickness compared to its extremely wide basal plane dimensions and its non-flatness or crumpled geometry in the nanofluids have the leading impacts on the effective TC properties of the Gr flake dispersed nanofluids. This modified model opens the new doors to analyse the insight of the thermophysical properties of various types of nanofluids by introducing potential other parameters